Pengaruh Profitabilitas, Ukuran Perusahaan dan Umur Perusahaan terhadap Audit Report Lag pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2016-2019 - Mia Nurulzanah; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research aims to examine the effect of profitability, firm size and firm age on audit report lag. The samples used in this study are manufacturing companies in the food and beverage sub- sector listed on the Indonesia Stock Exchange (IDX) in the 2016-2019 period, with a total population of 80 and a sample of 20 companies. Sampling was carried out using purposive sampling method with data analysis method using panel data regression method. The results of the analysis of the data obtained are that the profitability variable has a positive effect on audit report lag and the age of the company has a positive effect, while the firm size variable has a negative effect. Based on the results of the determination test, the value of the Adjusted R-Square is 0.475317, this means that it is equivalent to 47.5%. It can be explained by three independent variables (profitability, company size and age of the company) that affect the audit report lag. While the remaining 52.5% were influenced by other variables that were not researched by the researcher.